(3ebGdI LGdjfhS aj JTQjM GdCYVGA ddeJYdejfs - (3CHh YKeGf SYjO Hf jYbhH GdeTbjs
(3ChdgG (B:s
(3Efg bO jfHZi ddWHjH Cf jYQa gjFI cd hGMO ef GdYXGe ai faSg , hMGdg ai JQcjHI eY ZjQg , YfO GdJeGSg CMcGe YdGL s
(3BNQgG (B:s
(3hcPdc GdTYH GdChdi ef GdTQGjjf GdJi JSjQ Edi GdcHO hGdeYOI hGdWMGd hGdCeYGA , adjS jLGhQgG YQa Edi Cf jHJOF jfbSe s
(3jTJed Ydi GQHY ebGdGJs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B180 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs